KONTROSEPSI DAN STERILISASI DALAM PERNIKAHAN - Hayati, Yassir (JOURNAL EQUITABLE, 2018)
Contraception and sterilization in a marriage is a highly effective contraception and prioritized to space pregnancy, with this we can know what contraception and sterilization and anything only contraceptives that is safe to use in a marriage like pills, suntukan, implant / implant IUD / The IUD (intrauterine device), spermicides, condoms, diafragama, vagina pasta, and so forth, and in this paper we also can know the opinion of the scholars pengenai use of contraceptives and sertilisasi. While sterilization itself prohibited, because it can lead to infertility